Molecular Cloning and Analysis of the Regulation of Nit-3, the Structural Gene for Nitrate Reductase in Neurospora crassa - Fu, Ying-Hui; Marzluf, George A. (Proceedings of the National Academy of Sciences - PNAS, 1987)
The nit-3 gene of Neurospora crassa encodes the enzyme nitrate reductase and is regulated by nitrogen catabolite repression and by specific induction with nitrate. The nit-3 gene was isolated from a cosmid-based genomic library by dual selection for benomyl resistance and for the ability to complement a nit-3 mutant strain using the sibling-selection procedure. The nit-3 gene was subcloned as a 3.8-kilobase DNA fragment from a cosmid that carried an ≈ 40-kilobase N. crassa DNA insert. A restriction fragment length polymorphism analysis revealed that the cloned segment displayed tight linkage to two linkage-group-4 markers that flank the genomic location of nit-3. RNA gel blot analyses of RNA from wild-type and various mutant strains were carried out to examine the molecular mechanism for regulation of nit-3 gene expression. The nit-3 gene was transcribed to give a large mRNA of ≈ 3.4 kilobases, the expected size to encode nitrate reductase. The nit-3 gene was only expressed in wild-type cells subject to simultaneous nitrogen derepression and nitrate induction. A mutant of nit-2, the major nitrogen regulatory gene of Neurospora, did not have detectable levels of nit-3 gene transcripts under the exact conditions in which these transcripts were highly expressed in wild type. Similarly, a mutant of nit-4, which defines a minor positive-acting nitrogen control gene, failed to express detectable levels of the nit-3 transcript. Nitrate reductase gene expression was partially resistant to nitrogen repression in a mutant of the nmr gene, which appears to be a regulatory gene with a direct role in nitrogen catabolite repression. Results are presented that suggest that the enzyme glutamine synthetase does not serve any regulatory role in controlling nitrate reductase gene expression.